2007
DOI: 10.1152/ajpheart.00329.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic IL-6 infusion on acute pressor responses to vasoconstrictors in mice

Abstract: Interleukin (IL)-6 has been implicated as a contributing factor in the pathogenesis of hypertension, although the mechanisms involved are unclear. Studies conducted in vitro suggest that IL-6 may have a direct effect on vascular tone and may modulate constrictor responses to agonists. Whether this effect can be observed in vivo is unknown. Therefore, mice were treated with either IL-6 (16 ng/h sc) or vehicle for 14 days, and the acute blood pressure and heart rate responses to endothelin (ET)-1, angiotensin II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Our results showed that interleukin-6 plays a role in hypertension-induced end-organ damage, rather than in the development of hypertension per se . In this regard, our findings are consistent with previous reports showing that interleukin-6 did not affect acute pressor responsiveness to Ang II in vivo [11] and that infusion of interleukin-6 for 7 days did not modify BP [10]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that interleukin-6 plays a role in hypertension-induced end-organ damage, rather than in the development of hypertension per se . In this regard, our findings are consistent with previous reports showing that interleukin-6 did not affect acute pressor responsiveness to Ang II in vivo [11] and that infusion of interleukin-6 for 7 days did not modify BP [10]. …”
Section: Discussionsupporting
confidence: 93%
“…However, not all studies have shown a consistent detrimental effect of interleukin-6 on cardiovascular diseases. One study showed no effect of chronic infusion of interleukin-6 on pressure responsiveness to Ang II in vivo [11]. And another reported that deletion of interleukin-6 actually caused adverse cardiac remodeling, leading to myocardial fibrosis and failure [12], thus opening the possibility that the reported attenuation in Ang II-induced hypertension might be secondary to heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…This dose was similar to that used in the blood pressure measurements we performed. The diameter of control vessels contracted by 13.4 ± 2.6% 1 hour after dexamethasone while that of Tie-1 Cre+ vessels contracted by only 6.6 ± 0.5% (p=0.034, Figure 5) As a positive control, a separate cohort of Cre− (n=4) and Tie-1 Cre+ mice (n=4) were treated with phenylephrine 100 μg/kg, a dose that was found to result in hypertension in vivo [34]. In this case, the diameter of Cre− vessels contracted by 13.8 ± 2.8% 1 hour after phenylephrine administration while that of Tie-1 Cre+ vessels contracted similarly by 15.5 ± 2.6% (p=0.25).…”
Section: Resultsmentioning
confidence: 99%
“…The lower ET-1 values could reflect a favorable protective effect against angiopathy, since ET-1 is considered a very potent vasoconstrictor peptide with marked hypertensive, mitogenic and atherogenic effects [30,31]. ET-1 production is stimulated by several factors such as mechanical stimulation of the endothelium, lipids (high-density and low-density lipoproteins IGF-1 and IL-6) [32,33,34]. Since these factors were comparable in the two groups, other factors must be responsible for the lower ET-1 values in the CYP21A2 carriers.…”
Section: Discussionmentioning
confidence: 99%